Knowledge between academics about body donation for the teaching of Human Anatomy (Research, Society and Development, 2021)
The use of human corpses for teaching purposes is a common practice worldwide. The objective was to report the knowledge of academics on the donation of cadavers for the teaching of human anatomy. For that purpose 200 academics in the areas of biological sciences and health (CBS), exact sciences (CE), technological and agrarian sciences (CTA), and human and social sciences (CHS) answered an instrument developed by the authors. Male participants were more likely to donate their body or that of a family member (36.7% and 56.9% respectively). Knowledge about the use (98.0%) and how corpses are used (70.6%) in teaching activities (98.0%), as well as the agreement to use this resource (96.1%) were predominant among CBS academics. The results demonstrate a consensus on the importance of using cadavers in teaching, as most academics agree with teaching on cadavers and their use in the development of scientific medical research. The greatest knowledge regarding the preservation, manipulation and importance of the corpse for technical and humanized training is among CBS academics. Despite this, most academics expressed a desire not to donate their bodies.